Cerebral blood flow is associated with markers of neurodegeneration in Huntington's disease. (September 2022) - Rocha, Natalia P.; Charron, Odelin; Colpo, Gabriela D.; Latham, Leigh B.; Patino, Jorge E.; Stimming, Erin Furr; Freeman, Leorah; Teixeira, Antonio L.
Abstract: Introduction: The ultimate cause of neuronal death in Huntington's disease (HD) is still uncertain. Apart from impairment in systems handling abnormal proteins, other mechanisms might contribute to neurodegeneration and progression of HD. Decreased cerebral blood flow (CBF) has been described in other neurodegenerative disorders and may play a role in HD. Objectives: To investigate CBF changes in HD gene carriers. Methods: A group of 39 HD gene carriers (18 premanifest and 21 manifest HD) and 16 controls underwent a comprehensive clinical evaluation and a brain magnetic resonance imaging protocol that included pseudo-continuous arterial spin labeling to quantify CBF. Regions of interest (ROI) analyses were performed to compare CBF in controls vs premanifest HD vs manifest HD. Correlation analyses were performed to ascertain the relationship between CBF and clinical and biomarkers data. Results: We found a decrease in CBF in bilateral caudate and putamen of patients with manifest HD in comparison with controls. CBF of premanifest HD carriers in the same ROIs was midway between controls and the HD patients, with differences not reaching statistical significance. Lower CBF in caudate and putamen was associated with worse motor symptoms, functionality, and cognitive performance. CBF was also associated with markers of neurodegeneration: higher CBF in caudate and putamen significantly correlated to higher volumes in the same ROI and to lower levels of neurofilament light chain. Conclusion: As CBF changes in caudate and putamen nuclei were associated with markers of neurodegeneration and with clinical outcomes, decreased CBF and oxygen supply could emerge as a relevant mechanism contributing to degeneration in HD. Highlights: Decreased blood flow is an important feature in HD pathophysiology. Decreased blood flow is not evident in premanifest HD. Decreased oxygen supply may contribute to neurodegeneration in HD.